2020
DOI: 10.1371/journal.pone.0244059
|View full text |Cite|
|
Sign up to set email alerts
|

Seed germination ecology of Conyza stricta Willd. and implications for management

Abstract: Numerous cropping systems of the world are experiencing the emergence of new weed species in response to conservation agriculture. Conyza stricta Willd. is being a newly emerging weed of barley-based cropping systems in response to conservational tillage practices. Seed germination ecology of four populations (irrigated, rainfed, abandoned and ruderal habitats) was studied in laboratory and greenhouse experiments. The presence/absence of seed dormancy was inferred first, which indicated seeds were non-dormant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
3
4
0
Order By: Relevance
“…The differences in populations are direct effect of the environmental cues faced by the maternal plants. Plenty of literature is available that supports our results pertaining to differences among seed germination biology of different populations due to maternal environments [ 14 , 15 , 17 , 18 , 44 ]. However, genetic factors also mediate the germination traits of different populations.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The differences in populations are direct effect of the environmental cues faced by the maternal plants. Plenty of literature is available that supports our results pertaining to differences among seed germination biology of different populations due to maternal environments [ 14 , 15 , 17 , 18 , 44 ]. However, genetic factors also mediate the germination traits of different populations.…”
Section: Discussionsupporting
confidence: 71%
“…Our second hypothesis pertaining to the impacts of environmental cues on seed germination biology of the studied populations also stood valid and there are plenty of evidences to support our hypothesis [ 13 15 , 17 , 18 , 45 ]. Seeds of Conyza species require a definite light period for their successful seed germination.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…A recent study revealed that populations of erect horseweed [ Conyza stricta (Willd.)] can tolerate salinity and germinate under 0 to 500 mM NaCl levels of salinity (Ali et al 2020). In another study, it was found that C. bonariensis populations could germinate at an NaCl concentration of 200 mM, and germination was zero at 250 mM NaCl (Loura et al 2020).…”
Section: Introductionmentioning
confidence: 99%